PENGARUH HARGA, CITRA MEREK, KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK IMPLORA DIMEDIASI MINAT BELI - Fransiska; Dina Octaviani (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2023)
This research aims to analyze the influence of price, brand image and product quality on purchasing decisions for Implora products, by considering the role of purchasing interest as a mediator in this relationship. This research was conducted using a sample of Implora lipstick customers in Pontianak City. This research is quantitative descriptive. The total sample was 145 people, data was collected using a Likert scale questionnaire. The analysis technique uses Structural Equation Modeling and data processing in this research uses WarpPLS 8.0. The research results concluded that price had a positive and significant effect on purchasing decisions, brand image did not have a positive and significant effect on purchasing decisions. Product quality had a positive and significant effect on purchasing decisions for Implora products. In addition, purchase interest is proven not to mediate the relationship between price, brand image and product quality on purchasing decisions.